2014
DOI: 10.1007/s40502-014-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in leaf photosynthetic response of rice genotypes to post-anthesis water deficit

Abstract: Variation in the response of six diverse rice genotypes to imposed water stress was investigated in terms of leaf photosynthetic traits and leaf water potential measurements (W leaf ) during and following a period of water stress. The W leaf reduced from 0 days up to 6th day of irrigation deprivation and the reduction in W leaf was more pronounced in Swarna and minimum in PA-6201. A gradual recovery in W leaf was observed in all the tested varieties after re-irrigation. Similarly, water stress significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(38 reference statements)
3
5
1
Order By: Relevance
“…Carotenoids can facilitate the non-radiative dissipation of excitation energy and increase antioxidant protection (Stahl and Sies 2003), in the present work, carotenoids content was reduced at C50 mM NaCl, but the Chl t/Car ratio did not decrease in the presence of different NaCl levels except at 100 and 175 mM NaCl in contrast to another report, where Chl t/Car ratio decreased in Ginkgo tree leaves under open-field condition compared with shade enclosure condition (Wang et al 2014). Furthermore, the Chl t/Car ratio in different rice genotypes had different responses to water stress (Gauthami et al 2014). This indicated that chlorophyll content was more affected than that of carotenoids under abiotic stress, and it seems that the level of Chl t/Car ratio was different between cell level and the whole plant level, and a species or genus.…”
Section: Discussioncontrasting
confidence: 79%
“…Carotenoids can facilitate the non-radiative dissipation of excitation energy and increase antioxidant protection (Stahl and Sies 2003), in the present work, carotenoids content was reduced at C50 mM NaCl, but the Chl t/Car ratio did not decrease in the presence of different NaCl levels except at 100 and 175 mM NaCl in contrast to another report, where Chl t/Car ratio decreased in Ginkgo tree leaves under open-field condition compared with shade enclosure condition (Wang et al 2014). Furthermore, the Chl t/Car ratio in different rice genotypes had different responses to water stress (Gauthami et al 2014). This indicated that chlorophyll content was more affected than that of carotenoids under abiotic stress, and it seems that the level of Chl t/Car ratio was different between cell level and the whole plant level, and a species or genus.…”
Section: Discussioncontrasting
confidence: 79%
“…Results of the present study indicated that traditional landraces showed better photosynthetic efficiency but unable to increase grain yield, because increase in leaf photosynthesis may not necessarily leads to increase in grain yield (Gu et al 2013). In rice, higher leaf P N was reported to be correlated with gs and carboxylation capacity (Gauthami et al 2014). The WUE can be influenced by both variation in P N or E and both, which have been reported earlier in rice (Gauthami et al 2014).…”
Section: Resultssupporting
confidence: 62%
“…In rice, higher leaf P N was reported to be correlated with gs and carboxylation capacity (Gauthami et al 2014). The WUE can be influenced by both variation in P N or E and both, which have been reported earlier in rice (Gauthami et al 2014). There have been several reports that the incorporation of desired natural genetic variation in photosynthesis through breeding programmes, leads to increase in crop photosynthesis (Haritha et al 2017).…”
Section: Resultsmentioning
confidence: 84%
“…Photosynthesis forms an important aspect of plant metabolism and balance sheet of growth and development, which is known to be sensitive to drought and water deficit (Gauthami et al 2014). In this study, we evaluated the photosynthetic performance of the studied landraces of Koraput under different durations of drought.…”
Section: Discussionmentioning
confidence: 99%